FRI0191 IL17 Producing Non-T Cells in Patients with Enteropathic Spondyloarthropathy: The Association with Disease Activity. (9th June 2015) - Triggianese, P.; Conigliaro, P.; Chimenti, M.S.; Ballanti, E.; Perricone, R.; Biancone, L.; Pallone, F.; Monteleone, G.; Monteleone, I.
Abstract : Background: The association between Spondyloarthropathy (SpA) and Inflammatory Bowel Disease (IBD) is largely established. The coexistence of both conditions in patients (enteropathic SpA, SpAe) and the increased cross-risk ratios between SpA and IBD strongly suggest a shared pathophysiology. In SpAe patients, axial (ax) and peripheral (per) joint involvements are recognized. Both the innate and the adaptive immune responses are likely to contribute to the establishment of chronic inflammation. Peripheral blood CD45+ cells analyses have not been previously reported in patients with SpAe. Objectives: The objective of this study was to evaluate the frequencies of Tbet+/RORγ+/Foxp3+ expressing cells in peripheral blood CD45+CD3+ and CD45+CD3- cells from SpAe patients. Intracellular expression of IL4/IFNγ/IL17 was analyzed in both CD45+CD3+ and CD45+CD3- cells. Moreover we aim at evaluating the association between cell assessment and disease activity. Methods: 16 patients affected by SpAe (n=10 per, n=1 ax, n=5 both; n=9 Crhon's disease, n=6 ulcerative colitis, n=1 indeterminate colitis) were enrolled. All of them were naïve for treatment with biologic agents and none was on steroids. Patients' disease activity was recorded by DAS44-CRP, ASDAS-CRP and BASDAI whereas functional status was assessed by BASFI. Freshly isolated peripheral blood mononuclear cells were stained with fluorescent antibodies against cell-surface and intracellular markers to characterize cell subsets by flow cytometry. The frequencies of cells expressing transcriptional factors Tbet/RORγ/Foxp3 were evaluated in CD45+CD3- and CD45+CD3+ cells. The expression of IL4/IL17/IFNγ were recorded in CD45+CD3- and CD45+CD3+ cells after 4-hours in vitro stimulation with PMA and ionomicin. Ten sex- and age-matched healthy controls (HC) were also evaluated. Differences between mean values were determined by Student's t-test. The significance of correlations was determined by Pearson's correlation coefficient (r). Statistical analysis was considered significant when P values were less than 0.05 Results: The frequencies of CD45+CD3+ expressing Tbet/RORγ/Foxp3 were similar in SpAe patients and in HC. The same was registered analyzing IL4/IL17/IFNγ expressing cells. The proportion of CD45+CD3- cells expressing RORγ resulted significantly higher in the SpAe group than in the HC ( P <0.05, Figure 1A ); the same was found in the proportion of CD45+CD3- cells expressing IL17 ( P <0.05) (Figure 1B ). The frequency of CD45+CD3-IL17+ cells resulted positively related to DAS44-CRP levels (r=0.7, P =0.04, Figure 1C ) and BASFI (r=0.6, P <0.05, Figure 1D ) while no correlations resulted between cell assessment and ASDAS-CRP or BASDAI. Conclusions: The present study represents the first report regarding the assessment of the peripheral blood CD45+ cells in patients affected by SpAe. Our preliminary results may support the potential role of IL17 producing non-T cells dependent on RORγ in the pathogenesis of SpAe. References: Fantini MC, Pallone F, Monteleone G. Common mechanisms in inflammatory bowel disease and spondiloarthropathies. World J Gastroenterol 2009;15:2472-8. Monteleone I, Pallone F, Monteleone G. Th17-related cytokines: new players in the control of chronic intestinal inflammation. BMC Med 2011;15:9:122. Disclosure of Interest: None declared